Serum Neurofilament Light and GFAP Are Associated With Disease Severity in Inflammatory Disorders With Aquaporin-4 or Myelin Oligodendrocyte Glycoprotein Antibodies - Chang, Xuechun; Huang, Wenjuan; Wang, Liang; ZhangBao, Jingzi; Zhou, Lei; Lu, Chuanzhen; Wang, Min; Yu, Jian; Li, Haiqing; Li, Yuxin; Zhao, Chongbo; Lu, Jiahong; et al. (Frontiers in Immunology, 2021)
Objective: To evaluate the potential of serum neurofilament light (sNfL) and serum glial fibrillary acidic protein (sGFAP) as disease biomarkers in neuromyelitis optica spectrum disorder (NMOSD) with aquaporin-4 antibody (AQP4-ab) or myelin oligodendrocyte glycoprotein-antibody-associated disease (MOGAD). Methods: Patients with AQP4-ab-positive NMOSD (n = 51), MOGAD (n = 42), and relapsing-remitting multiple sclerosis (RRMS) (n = 31 for sNfL and n = 22 for sGFAP testing), as well as healthy controls (HCs) (n = 28), were enrolled prospectively. We assessed sNfL and sGFAP levels using ultrasensitive single-molecule array assays. Correlations of sNfL and sGFAP levels with clinical parameters were further examined in AQP4-ab-positive NMOSD and MOGAD patients. Results: sNfL levels were significantly higher in patients with AQP4-ab-positive NMOSD (median 17.6 pg/mL), MOGAD (27.2 pg/mL), and RRMS (24.5 pg/mL) than in HCs (7.4 pg/mL, all p < 0.001). sGFAP levels were remarkably increased in patients with AQP4-ab-positive NMOSD (274.1 pg/mL) and MOGAD (136.7 pg/mL) than in HCs (61.4 pg/mL, both p < 0.001). Besides, sGFAP levels were also significantly higher in patients with AQP4-ab-positive NMOSD compared to those in RRMS patients (66.5 pg/mL, p < 0.001). The sGFAP/sNfL ratio exhibited good discrimination among the three disease groups. sNfL levels increased during relapse in patients with MOGAD (p = 0.049) and RRMS (p < 0.001), while sGFAP levels increased during relapse in all three of the disease groups (all p < 0.05). Both sNfL and sGFAP concentrations correlated positively with Expanded Disability Status Scale scores in AQP4-ab-positive NMOSD (β = 1.88, p = 0.018 and β = 2.04, p = 0.032) and MOGAD patients (β = 1.98, p = 0.013 and β = 1.52, p = 0.008). Conclusion: sNfL and sGFAP levels are associated with disease severity in AQP4-ab-positive NMOSD and MOGAD patients, and the sGFAP/sNfL ratio may reflect distinct disease pathogenesis.